2022
DOI: 10.1093/ajcn/nqac033
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin M1 in milk does not contribute substantially to global liver cancer incidence

Abstract: Background For 60 y, it has been known that aflatoxin B1 (AFB1), a mycotoxin produced by Aspergillus fungi in certain food and feed crops, causes hepatocellular carcinoma (liver cancer; HCC) in humans. The annual global burden of AFB1-related HCC has been estimated. However, much less is known about the potential carcinogenic impact of a metabolite of AFB1 called aflatoxin M1 (AFM1), which is secreted in milk when dairy animals consume AFB1-contaminated feed. The cancer risk of AFM1 to humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…Increased aflatoxin exposure is linked to increased liver cancer risk in humans [16], and field corn produced in the US is in part used for human food both in the US and worldwide. Additionally, increased aflatoxin in dairy animal feed is linked to higher levels of a metabolite aflatoxin M1 in milk [45], which-although not associated with significant human cancer risk [46]may nonetheless cause toxicological effects not yet elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Increased aflatoxin exposure is linked to increased liver cancer risk in humans [16], and field corn produced in the US is in part used for human food both in the US and worldwide. Additionally, increased aflatoxin in dairy animal feed is linked to higher levels of a metabolite aflatoxin M1 in milk [45], which-although not associated with significant human cancer risk [46]may nonetheless cause toxicological effects not yet elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study will inform researchers and policymakers on the impact of AFM 1 in milk on children’s nutrition outcomes and will have implications for the transforming dairy value chains in Ethiopia. Ethiopia has recently adopted strict AFM 1 standards in milk and other dairy products, which has led to dairy farmers dumping their milk instead of selling it in the market 12. An earlier study showed that cancer risk from AFM 1 consumption was expected to be extremely low 12.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, milk can harbour multiple contaminants such as AFM 1 . AFB 1 , the parent compound of AFM 1 , may impair child growth9 through several pathways such as disruption of insulin-like growth factors,10 intestinal damage11 and immunosuppressive effects that increase infection susceptibility 12 13. Whether AFM 1 could cause similar effects is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFs have been reported to play a causative role in 4.6-28.2% of the global HCC cases via consumption of contaminated food (Liu & Wu, 2010). Moreover, AF metabolites such as AFM1 has recently been quantified to cause ~13-32 HCC cases/year/100,000 population/ng AFM1 consumed, globally (Saha Turna et al, 2022). Growth impairment is another adverse effect that has been linked with chronic dietary exposure to AFs through breastmilk, infant formula and weaning foods during the early stages of life (Ahlberg et al, 2018;Saha Turna & Wu, 2019) and is a major concern for developing or low/middle income countries where high AF prevalence rates are observed.…”
Section: Introductionmentioning
confidence: 99%